2004
DOI: 10.1111/j.1600-051x.2004.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Significant influence of scaler tip design on root substance loss resulting from ultrasonic scaling: a laserprofilometric in vitro study

Abstract: The present investigation could demonstrate that the aggressiveness of magnetostrictive and piezoelectric ultrasonic devices to root substance was significantly influenced by the scaler tip designs, increasing for wider scaler tips as compared with narrow, probe-shaped inserts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 15 publications
3
41
0
Order By: Relevance
“…For clinicians, this work demonstrates that the type of generator mechanism (magnetostrictive or piezoelectric) does not affect the pattern of oscillation of the ultrasonic probe. What will have more of a potential influence on the clinical result is the shape and design of the probe, which has been shown previously to affect root surfaces (Jepsen et al 2004). Future studies should consider this aspect of the ultrasonic scaler as a factor affecting tooth surface defects.…”
Section: Discussionmentioning
confidence: 99%
“…For clinicians, this work demonstrates that the type of generator mechanism (magnetostrictive or piezoelectric) does not affect the pattern of oscillation of the ultrasonic probe. What will have more of a potential influence on the clinical result is the shape and design of the probe, which has been shown previously to affect root surfaces (Jepsen et al 2004). Future studies should consider this aspect of the ultrasonic scaler as a factor affecting tooth surface defects.…”
Section: Discussionmentioning
confidence: 99%
“…These damages increase exponentially as the ultrasonic power is increased from medium to high. It is also revealed that instrument contact time, angulations and design of the tip, tip to tooth angle, power level of the unit, sharpness of the working edge, instrument pressure are important on the degree of root damage (43–45).…”
Section: Sonic and Ultrasonic Scalersmentioning
confidence: 99%
“…However, root and dentin surfaces are also vulnerable to physical injury. Because of the low mineral content, root surfaces are easily abraded by toothbrushing, and although cementum formation triples throughout life, reaching a thickness of about 50 μm in the coronal part of the root at the age of 20 [Furseth and Mjör, 1979], exposed cervical root cementum is often damaged and/or removed by regular scaling and root planing [Jepsen et al, 2004]. Therefore, in clinical circumstances the exposed root often presents a dentin surface.…”
Section: Structural Composition Of Root and Dentin Surfacesmentioning
confidence: 99%